2022
DOI: 10.1136/jitc-2022-004784
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 7/8 agonist R848 alters the immune tumor microenvironment and enhances SBRT-induced antitumor efficacy in murine models of pancreatic cancer

Abstract: BackgroundStereotactic body radiotherapy (SBRT) has been increasingly used as adjuvant therapy in pancreatic ductal adenocarcinoma (PDAC), and induces immunogenic cell death, which leads to the release of tumor antigen and damage-associated molecular patterns. However, this induction often fails to generate sufficient response to overcome pre-existing tumor microenvironment (TME) immunosuppression. Toll-like receptor (TLR) 7/8 ligands, such as R848, can amplify the effect of tumor vaccines, with recent evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…In pancreatic cancer, TLR2 and TLR4 were found mainly over-expression and correlated with more mortality [10], while TLR9 was found low express in pancreatic cancer [11]. Other molecules of the TLR family (TLR3,7,8) were also con rmed to be closely related to occurrence, development and invasion of pancreatic cancer [12,13]. Therefore, we speculated that TLR2 interference can similarly regulate tumor microenvironment so as to minimize pancancer cell growth and attenuate metastasis, which would be a good candidate of pancreatic cancer medical therapy.…”
Section: Introductionmentioning
confidence: 88%
“…In pancreatic cancer, TLR2 and TLR4 were found mainly over-expression and correlated with more mortality [10], while TLR9 was found low express in pancreatic cancer [11]. Other molecules of the TLR family (TLR3,7,8) were also con rmed to be closely related to occurrence, development and invasion of pancreatic cancer [12,13]. Therefore, we speculated that TLR2 interference can similarly regulate tumor microenvironment so as to minimize pancancer cell growth and attenuate metastasis, which would be a good candidate of pancreatic cancer medical therapy.…”
Section: Introductionmentioning
confidence: 88%
“…As previously described, 17 tumor tissue samples were homogenized and digested with Lysis Buffer #11 (R&D Systems) containing protease inhibitors on ice for 1 hour. The samples were then centrifuged at 14,000 rpm for 20 min at 4 o C, and supernatants were collected and then delivered to Eve Technologies Corporation (Calgary, AB.…”
Section: Methodsmentioning
confidence: 99%
“…In a predefined group of patients with high metastatic burden, the IMM‐101/gemcitabine combination significantly prolonged mOS from 4.4 to 7.0 months [61]. Similarly, in another study, the TLR7/8 agonist R848 showed the potential opportunity to target metastatic PDAC by combining with stereotactic body radiotherapy [62]. This response to a TLR agonist may be associated with modulation of the immunosuppressive microenvironment by increasing cytotoxic CD8 + T‐cells in the metastatic microenvironment and improving therapeutic outcomes [62].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in another study, the TLR7/8 agonist R848 showed the potential opportunity to target metastatic PDAC by combining with stereotactic body radiotherapy [62]. This response to a TLR agonist may be associated with modulation of the immunosuppressive microenvironment by increasing cytotoxic CD8 + T‐cells in the metastatic microenvironment and improving therapeutic outcomes [62]. This suggests combination TLR agonists may be useful in downstaging late‐stage/metastatic PDACs, potentially in preparation for surgical resection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation